2011
DOI: 10.1111/j.1365-2036.2011.04625.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical predictors of small intestinal bacterial overgrowth by duodenal aspirate culture

Abstract: SUMMARY BackgroundThere has been increasing interest in small intestinal bacterial overgrowth (SIBO) after reports of a link with irritable bowel syndrome (IBS), yet our understanding of this entity is limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
91
4
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(109 citation statements)
references
References 35 publications
6
91
4
8
Order By: Relevance
“…In one published study there was a correlation between orocecal transit by scintigraphy and lactulose hydrogen breath test suggesting that gut motility changes, not SIBO, explained the positive breath tests in IBS [23]. Two additional studies looking at duodenal aspirate cultures in patients found conflicting results, with one providing evidence that SIBO was unusual in IBS [24] and the other suggesting that SIBO was more common in patients with diarrhea-predominant IBS (37.5%) compared with controls without diarrhea (27.3%) [25]. …”
Section: Discussionmentioning
confidence: 99%
“…In one published study there was a correlation between orocecal transit by scintigraphy and lactulose hydrogen breath test suggesting that gut motility changes, not SIBO, explained the positive breath tests in IBS [23]. Two additional studies looking at duodenal aspirate cultures in patients found conflicting results, with one providing evidence that SIBO was unusual in IBS [24] and the other suggesting that SIBO was more common in patients with diarrhea-predominant IBS (37.5%) compared with controls without diarrhea (27.3%) [25]. …”
Section: Discussionmentioning
confidence: 99%
“…In another study, duodenal fluids were endoscopically collected from 148 IBS patients. Bacterial volume of ≥10 5  cfu/mL was detected in only 2% of IBS patients, whereas in the control group (n=542), over 10% of people had SIBO 10. Tests that measure actual bacterial volume do not help demonstrate the relationship between IBS and SIBO.…”
Section: Introductionmentioning
confidence: 93%
“…The factors can be divided into anatomical (stenoses -strictures, blind loop, diverticulum, duplication), associated with disturbances to the function (diabetic autonomic neuropathy, intestinal pseudo-obstruction syndrome, systemic scleroderma, achlorhydria, slow gastrointestinal motility), and conditions predisposing to the development of bacteria (primary and secondary immunodeficiency, intestinal fistulas, achlorhydria, removal of the ileocecal valve) [22]. It is said that advanced age, use of narcotics, IBD, steatorrhea, intestinal diverticula and pancreatitis are more frequent in the group of patients with SIBO, which can be established through microbiological analysis -cultures of duodenal aspirates [23].…”
Section: Pathogenesismentioning
confidence: 99%